First report of begomoviruses infecting Cucumis sativus L. in North America and identification of a proposed new begomovirus species - Sanchez-Chavez, Sarahi; Regla-Marquez, Carlos Fernando; Cardenas-Conejo, Zugey Elizabeth; Garcia-Rodriguez, Daniel Alejandro; Centeno-Leija, Sara; Serrano-Posada, Hugo; Liñan-Rico, Andromeda; Partida-Palacios, Brenda Lizet; Cardenas-Conejo, Yair (PeerJ, 2020)
Background Members of the Begomovirus genus are phytopathogens that infect dicotyledonous plants, producing economic losses in tropical and subtropical regions. To date, only seven species of begomoviruses (BGVs) infecting cucumber have been described. Most cucumber infections were reported in South Asia. In the Americas, begomoviral infections affecting cucumber are scarce; just one report of begomovirus has been described in South America. The presence of whitefly and typical symptoms of viral infections observed in a cucumber field in Colima, Mexico, suggested that plants in this field were affected by BGVs. Methods To identify the BGVs infecting cucumber, we performed a high-throughput sequencing and compared the assembled contigs against the GenBank nucleic acid sequence database. To confirm the presence of viruses in cucumber samples, we performed a PCR detection using specific oligonucleotides. We cloned and sequenced by Sanger method the complete genome of a potential new begomovirus. Begomovirus species demarcation was performed according to the International Committee on Taxonomy of Viruses. The evolutionary relationship of the new virus was inferred using phylogenetic and recombination analyses. Results We identified five species of begomovirus infecting plants in a field. None of these have been previously reported infecting cucumber. One of the five species of viruses here reported is a new begomovirus species. Cucumber chlorotic leaf virus, the new species, is a bipartite begomovirus that has distinctive features of viruses belonging to the squash leaf curl virus clade. Conclusions The findings here described represent the first report of begomoviral infection affecting cucumber plants in North America. Previous to this report, only seven begomovirus species have been reported in the world, here we found five species infecting cucumber plants in a small sample suggesting that cucumber is vulnerable to BGVs. One of these viruses is a new species of begomovirus which is the first begomovirus originally isolated from the cucumber. The findings of this report could help to develop strategies to fight the begomoviral infections that affect cucumber crops.
Keywords: Geminivirus; Begomovirus; ssDNA virus; High-Throughput Sequencing; Cucumber